How can the combination of entrepreneurship policies activate regional innovation capability? A comparative study of Chinese provinces based on fsQCA - Yangjie Huang; Sihui Li; Xiyuan Xiang; Yajing Bu; Yang Guo (Journal of Innovation & Knowledge (JIK), 2022)
The global innovation environment is undergoing major changes. Driven by its entrepreneurship policy, China's innovation level has gradually improved, but the regional gap remains large. As previous studies mainly focused on the net impact of entrepreneurship policy on innovation, knowledge on the combination of entrepreneurship policies to improve regional innovation capability is still lacking. To fill this gap in the literature, this study uses fuzzy set qualitative comparative analysis (fsQCA) on data from 31 provinces in China to explore how five entrepreneurship policies (i.e., technology transfer, fiscal and tax, digital transformation, talent, and government innovation management policy) jointly affect regional innovation capability. The results show that these five entrepreneurship policies are sufficient conditions for high regional innovation capability, and three paths can produce high innovation capability. Therefore, local governments need to formulate appropriate entrepreneurship policies to address the actual situation. This study has important management significance for formulating entrepreneurship policies worldwide, especially in developing countries.
Keywords: M13; O38; R58; 650; Innovation capability; Entrepreneurship policy; Configuration perspective; Qualitative comparative analysis; Regional innovation system